Biocomputational Genome-Wide Identification Of Srna In Leptospira Interrogans Serovar Lai - Tan, Xinq Yuan (2019)
Regulatory small RNA (sRNA) is an RNA transcript that is not translated to protein but acts as a cell function. In bacteria, they are involved in various processes of biological cell modulation, for example in response to general stress, quorum sensing and virulence. The importance of sRNAs in various biological controls has led to their discovery in bacterial species such as Salmonella enterica, Mycobacterium tuberculosis and Vibrio cholera, over the past decade. The pathogenic Leptospira, a spirochaetal zoonosis disease, causes Leptospirosis, an epidemic that contributes to death and mobility worldwide, especially in Southeast Asia. These bacteria can adapt to a variety of stressful environments, for example in infected hosts or in low nutrient conditions. sRNAs are expected to play a regulatory role in the physiology of pathogenic Leptospira. sRNAs have been successfully discovered and archived cost-effectively and effectively through the consensus and advances in computing technology. In this study, RNAz-nocoRNAc, a proven success of the sRNA prediction program, was selected to screen the genome of Leptospira interrogans serovar Lai. As a result, a total of 126 sRNAs were predicted. Results compared to RNA-seq data were generated in previous studies and found that 7 sRNAs were expressed in the mid-log phase, stationary, serum pressure, temperature and iron pressure and 2 sRNA expression in all phases except iron pressure. RT-PCR confirmed that all of these sRNAs were expressed in the mid-log phase maintained in Leptospira spp. their function was predicted by TargetRNA2 and one candidate was predicted to target various resistance drugs mRNA. Experimental functional studies are necessary in the future to determine the regulatory role of sRNAs.